Every child matters? An evaluation of 'special educational needs' programmes in England - Francois Keslair; Eric Maurin; Sandra McNally (Institute for the Study of Labor (IZA), 2011)
The need for education to help every child rather than focus on average attainment has become a more central part of the policy agenda in the US and the UK. Remedial programmes are often difficult to evaluate because participation is usually based on pupil characteristics that are largely unobservable to the analyst. In this paper we evaluate programmes for children with moderate levels of 'special educational needs' in England. We show that the decentralized design of the policy generates significant variations in access to remediation resources across children with similar prior levels of difficulty. However, this differential is not reflected in subsequent educational attainment suggesting that the programme is ineffective for 'treated' children. In the second part of our analysis, we use demographic variation within schools to consider the effect of the programme on whole year groups. Our analysis is consistent with no overall effect on account of the combined direct and indirect (spillover) effects. Thus, the analysis suggests that a key way that English education purports to help children with learning difficulties is not working.
urn:nbn:de:101:1-201111072833
Keywords: I2; 330; education; special needs; evaluation; Bildungspolitik; Kinder; Bildungsniveau; Wirkungsanalyse; Großbritannien